A Comparative Analysis of Contribution of Human Resource Management to Organizational Performance of Banks in Serbia - Jelena, Vemic-Djurkovic; Jotic, Jelena; Maric, Radenko M (Industrija, 2013)
The contribution of this paper is in identification, proving and presentation of practice quality of human resource management as an important factor for achieving organizational effectiveness of banks. A group of correlations has been defined in this paper to be measured in order to reflect the impact of HRM practice on the effectiveness of banks in Serbia, which can lead to better functioning of not only banking organizations, but also of all other organizations in our environment and under current circumstances. The results of this study showed that banking organizations that have better HRM practices possess a more competitive workforce and better organizational performances, which further highlight the need for a more systematized and institutionalized use of human resources within commercial banking sector in Serbia